﻿Descriptions of two new flightless species of Pseudocsikia Schimmel & Platia (Coleoptera, Elateridae, Dimini) from Taiwan Island, China, with a definition of the formosana species-group - Lu Qiu; Robin Kundrata (ZooKeys, 2022)
Two new flightless click beetle species, Pseudocsikia choui sp. nov. and Pseudocsikia chanjuan sp. nov., are described and illustrated from Taiwan, China. Their habitus and diagnostic characters are illustrated. The two species most resemble P. formosana, which is endemic to Taiwan, by the strongly protruding pronotal anterior angles accompanied by pits and the shape of aedeagus. They can be all grouped as the P. formosana-species group. A key to the species of the P. formosana-species group and an updated checklist of Chinese Pseudocsikia with supplementary notes on type localities are provided. The discovery of two new species highlights the potential species-richness of the flightless click-beetles on Taiwan Island.